Studi Deskriptif Eksploratif Kejadian IUFD - Septerina P W; Puji Hastuti; Rusmini Rusmini (Jurnal LINK, 2015)
The purpose of this study was to describe the incidence of IUFD in hospitals Goeteng Purbalingga. This research is a descriptive study. The population of all women giving birth with IUFD from January through August 2014. Samples were some 26 people. The sampling technique with a total sampling. The characteristics of mothers were based on age 76.9% is not at risk , based on parity 53,8% multiparous. The causes of women giving birth with IUFDwere 38 ,5% are maternal factors, 46,2% are of fetal factors, 30,8% are placental factors. 50 % of maternal were caused by infection, 33,3% due to infection, and 75% due to placental abnormalities of the umbilical cord. It is suggested for Hospital to provide health education about the signs and symptom of danger in pregnancy.